The Mother Goddess of Champa: Po Ina Nagar - Noseworthy, William B (수완나부미, 2015)
This article utilizes interdisciplinary methods in order to critically review the existing research on the Mother Goddess of Champa: Po Ina Nagar. In the past, Po Ina Nagar has too often been portrayed as simply a "local adaptation of Uma, the wife of Siva, who was abandoned by the Cham adapted by the Vietnamese in conjunction with their conquest of Champa." This reading of the Po Ina Nagar narrative can be derived from even the best scholarly works on the subject of the goddess, as well as a grand majority of the works produced during the period of French colonial scholarship. In this article, I argue that the adaption of the literary studies strategies of "close reading", "surface reading as materiality", and the "hermeneutics of suspicion", applied to Cham manuscripts and epigraphic evidence-in addition to mixed anthropological and historical methods-demonstrates that Po Ina Nagar is, rather, a Champa (or ``Cham``) mother goddess, who has become known by many names, even as the Cham continue to re-assert that she is an indigenous Cham goddess in the context of a majority culture of Thanh Mau worship.